2016
DOI: 10.1021/acs.nanolett.6b00636
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Magnesium Phosphate Nanosheets Form Highly Thixotropic Gels That Up-Regulate Bone Formation

Abstract: Hydrogels composed of two-dimensional (2D) nanomaterials have become an important alternative to replace traditional inorganic scaffolds for tissue engineering. Here, we describe a novel nanocrystalline material with 2D morphology that was synthesized by tuning the crystallization of the sodium-magnesium-phosphate system. We discovered that the sodium ion can regulate the precipitation of magnesium phosphate by interacting with the crystal's surface causing a preferential crystal growth that results in 2D morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 62 publications
(137 reference statements)
6
36
0
Order By: Relevance
“…These results suggested that nanoengineered (NE) hydrogel‐based 2D nanomaterials acting as bioactive substitutes may have great potential for load‐bearing tissue applications. However, such 2D nanomaterials are characterized by insufficient degradation and bioresorption in vivo, which may be a concern for tissue engineering and biomedical applications …”
Section: Introductionmentioning
confidence: 99%
“…These results suggested that nanoengineered (NE) hydrogel‐based 2D nanomaterials acting as bioactive substitutes may have great potential for load‐bearing tissue applications. However, such 2D nanomaterials are characterized by insufficient degradation and bioresorption in vivo, which may be a concern for tissue engineering and biomedical applications …”
Section: Introductionmentioning
confidence: 99%
“…The combination of phosphate ions and metal elements creates abundant metal phosphate materials. The development of nanotechnology has spawned a series of metal phosphate nanomaterials, mainly calcium phosphate nanomaterials (CaPs), [89][90][91] hydroxyapatite nanomaterials, 92,93 manganese phosphate nanomaterials (MnPs), 94,95 magnesium phosphate nanomaterials (MgPs), 96,97 and zirconium phosphate nanomaterials (ZrPs). 98,99 These metal phosphate nanomaterials also present excellent biocompatibility and biodegradability.…”
Section: Metal Phosphide Nanomaterialsmentioning
confidence: 99%
“…In addition, some novel types of nanosheets are developed specifically for cell culture and tissue engineering. Laurenti et al developed a magnesium phosphate nanosheet-based thixotropic gel, and osteoblast cells could adhere onto the 2D structures and form colonies [ 33 ]. Functionalized nanosheets were also synthesized onto traditional medical materials for improving cell culture.…”
Section: Nanosheets As a Substratementioning
confidence: 99%